The role of leptin in obesity and diabetes mellitus in dog - Santos, Patrícia Isabel Cunha (2014)
Canine obesity is a serious breeding and health issue. Recent studies reported that 34-59% of dogs visiting veterinary are overweight and 5-20% are obese. Recent studies have shown that during the development of obesity there is several alterations at the cellular and molecular levels that contribute to the secretion of local and systemic molecules, called adipokines. These molecules contribute to the existence of a chronic low grade inflammatory state, to angiogenesis, to the control of appetite and satiety and to the control of the glucose and lipid metabolism. Together, these alterations may explain the reduced life span of obese animals and the development of several pathologies. One of main adipokines is leptin that plays a key role in the regulation of body weight, energy balance and feeding behaviour. Leptin is mainly regulated by adiposity, existing a positive correlation between the degree of adiposity and the plasma leptin concentration. In addition to adiposity, others factors regulate the leptin production such as insulin, glucocorticoids, endotoxin, and cytokines. Due to the contribution of leptin to the metabolism of glucose and lipids, several studies suggested that it may to establish an association between obesity, insulin resistance and ultimately diabetes. In fact, in humans the occurrence of obesity, dyslipidaemia and hypertension has been long associated to the development of insulin resistance and diabetes. However, the association between canine obesity and diabetes is not well understood, and there is no consensus whether obesity induces diabetes. Considering that obesity and diabetes reduce life span and the mechanisms underlying its development are not clearly understood, in this article we review the current knowledge on the association between obesity, diabetes and leptin.